A Multi-Scale, Participatory Approach to Developing a Protected Area Wetland Inventory in South Africa - Job, Nancy; Roux, D. J.; Bezuidenhout, H.; Cole, N. S. (Frontiers in Environmental Science, 2020)
Given limited time, staffing and specialist expertise, management of wetlands within biodiversity-rich protected areas of developing countries is often held back by a lack of information on the extent and nature of wetland resources. Rapid, realistic and effective wetland ecosystem assessment methods are needed to develop a baseline for monitoring that detects trends and guides management. Lack of available in-house wetland expertise stimulated a novel team which harnessed wide-ranging complementary and, ultimately, indispensable expertise, spanning all branches of the park, including park management and rangers, Scientific Services and Biodiversity Social Projects. Within a year, the team developed a sufficiently comprehensive inventory which captured the variation of wetlands present in Mountain Zebra National Park, South Africa. A total of 267 wetlands were mapped, while 62 were visited in the field and assessed through rapid verification. Careful collation of existing data and imagery informed a catchment approach, an emphasis on wetland-landscape connectivity, and strategic targeting of a sub-set of important and representative sites deserving of targeted, high effort field assessment. The remaining wetlands not visited in the field were subject to desktop review. Overall, this resulted in a comprehensive overview assessment of the entire Park at multiple scales. The approach of convening a multi-disciplinary team supports strengthened governance and integrated implementation of the findings into park planning, management and rehabilitation. The process provides a potential template for rolling out similar work in other parks and other areas that have limited funding and capacity.